2017
DOI: 10.1038/srep43627
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 predicts poor prognosis for nasopharyngeal carcinoma irrespective of PD-1 and EBV-DNA load

Abstract: Programmed death-1 (PD-1) is an immunosuppressive receptor functionally bound with programmed death-ligand 1 (PD-L1), which has been reported in various malignancies. However, only a few studies are available for the clinical significance of PD-1/PD-L1 in nasopharyngeal carcinoma (NPC). In this study, we aim to investigate alterations in PD-1/PD-L1 by using immunohistochemistry analysis in a cohort of consecutively enrolled NPC patients (n = 99). To further analyse the correlation between PD-1/PD-L1 and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 55 publications
(91 reference statements)
9
56
2
Order By: Relevance
“…Previous studies have suggested that the number of PD-1 + TILs is associated with the survival in patients with breast cancer and gastric cancer (21,22). However, others have suggested that the number of PD-1 + TILs was not associated with the survival in patients with nasopharyngeal carcinoma (23). In the present study, there were no relationships between the number of PD-1 + TILs and survival.…”
Section: Kaplan-meier Survival Curves According To the Pd-1/cd8 Ratiocontrasting
confidence: 51%
“…Previous studies have suggested that the number of PD-1 + TILs is associated with the survival in patients with breast cancer and gastric cancer (21,22). However, others have suggested that the number of PD-1 + TILs was not associated with the survival in patients with nasopharyngeal carcinoma (23). In the present study, there were no relationships between the number of PD-1 + TILs and survival.…”
Section: Kaplan-meier Survival Curves According To the Pd-1/cd8 Ratiocontrasting
confidence: 51%
“…Given the risk of immune‐related adverse events with treatment, having an accurate biomarker is a step towards personalizing immunotherapy that could mitigate this risk by allowing stratification of clinical responders and influence further patient treatment selection . Based on recent clinical evidence future trials should analyse PD‐L1 and HLA expression, EBV DNA clearance, Treg infiltration and tumour mutation burden rates . To illustrate this, Figure shows a marked improvement in PFS for the nivolumab NCI‐9742 trial when stratified by loss of HLA expression (1 year PFS 76% [yellow line] vs .…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of positive PD‐L1 expression in tumor cells was 76‐100% . Patients with high PD‐L1 expression in tumor cells had worst survival outcomes .…”
Section: Discussionmentioning
confidence: 99%